Handbook of dialysis - Daugirdas, John T.; Blake, Peter Gerard, 1956-; Ing, Todd S. (Lippincott Williams and Wilkins handbook., 2015)
"Handbook of Dialysis is now completely revised in its Fifth Edition. It continues to provides practical, accessible information on all aspects of dialysis with emphasis on day-to-day patient management. Authored by international experts, chapters provide complete coverage of hemodialysis, peritoneal dialysis, special problems in dialysis patients, and problems pertaining to various organ systems"--Provided by publisher